Byzantine Emperor John I Comnenus in light of the book of John Cynamos 512-538 AH / 1118-1143 AD (Damascus University Journal of Historical Studies, 2025)
The sixth century AH/twelfth century AD witnessed the arrival of the Komnene family to rule the Byzantine Empire, whichh was able to leave Immortal pages in history, especially In the pages of their contemporary historians, including John Kynamos, who chronicled the rule of the two emperors, John Komnene and his son Manuel Komnene, and praised them greatly, but he dealt with the reign of John Komnene.  In short, while Manuel Komnene has been chronicled at great length, John Komnene was one of the most prominent emperors who ascended the throne of the Byzantine Empire throughout its long history and one of the greatest figures who ruled with intelligence and wisdom. The research shed light on the works of John Komnene in the book Kynamos, especially his accession to the throne, and his wars in Asia Minor. Against the Seljuks, his wars In the Balkans against the Hungarians and Serbs, and his campaign to obtain Antioch. The research also dealt with John’s campaign in Cilicia against Leo the Armenian, and shed light on the transfer of power from John Komnene to his younger son Manuel Komnene and then the death of John.
Keywords: The Komnene family; the Byzantine Empire; John Komnene; Manuel Komnene; John Cynamos; the emperors